Microwave subsurface imaging of buried objects under a rough air–soil interface - Akıncı, Mehmet Nuri; Çayören, Mehmet (Informa UK Limited, 2014)
We consider subsurface imaging of buried objects under a rough air–soil interface and present a microwave imaging method that is capable of determining the geometrical properties of multiple objects without requiring any a-priori information on the objects. The theoretical background of the method relies on factorization of scattering operators and the locations of buried objects are qualitatively determined from limited aperture near-field measurements performed with a short antenna array moving over the investigated region. The numerical results demonstrate that the method can handle very rough interfaces, provided that they are exactly known, and accurately determine the locations of buried obstacles even while the measurements are still in progress, which in turn opens up the possibility of real-time operation.